2020
DOI: 10.1177/0888406419880353
|View full text |Cite
|
Sign up to set email alerts
|

Improving Working Conditions to Support Special Educators’ Effectiveness: A Call for Leadership

Abstract: Special education teachers (SETs) are expected to use effective practices to improve outcomes for students with disabilities, yet even those who are well-prepared may not be effective in teaching these students, as problematic working conditions may limit their opportunities to teach effectively and their longevity in the profession. To complicate matters, the context of SETs’ work has changed, calling into question the nature of their roles in supporting student learning. The purpose of this article is to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 75 publications
(135 reference statements)
2
52
0
Order By: Relevance
“…Given their limited preparation to teach SWDs, it seems plausible that SETs in high poverty settings who are not well-prepared for their work are serious attrition risks. Nevertheless, it is noteworthy that high-poverty schools are staffed by larger proportions of SETs of color (Billingsley, Bettini, Mathews, & McLeskey, in press) and teachers of color may have higher retention rates in these schools than White teachers in high-poverty schools, and higher retention rates than teachers of color in low-poverty schools (Carver-Thomas, 2018).…”
Section: Specific Aspects Of the Set Shortage Problemmentioning
confidence: 99%
“…Given their limited preparation to teach SWDs, it seems plausible that SETs in high poverty settings who are not well-prepared for their work are serious attrition risks. Nevertheless, it is noteworthy that high-poverty schools are staffed by larger proportions of SETs of color (Billingsley, Bettini, Mathews, & McLeskey, in press) and teachers of color may have higher retention rates in these schools than White teachers in high-poverty schools, and higher retention rates than teachers of color in low-poverty schools (Carver-Thomas, 2018).…”
Section: Specific Aspects Of the Set Shortage Problemmentioning
confidence: 99%
“…One key issue for special educators is access to curricular resources and training, which can create either positive or negative working conditions (Bettini, Cumming, et al, 2020; Billingsley et al, 2020). When special education teachers are provided with curricular resources, such as textbooks, instructional materials, and scope and sequence, studies have shown a projected reduction in stress and teachers identified they are more likely to stay in the profession.…”
Section: The Importance Of Curricular Resourcesmentioning
confidence: 99%
“…When special education teachers are provided with curricular resources, such as textbooks, instructional materials, and scope and sequence, studies have shown a projected reduction in stress and teachers identified they are more likely to stay in the profession. On the other hand, when access to curricular resources is low, teachers are more likely to report high levels of stress and burnout with an increased desire to leave the job (Bettini, Cumming, et al, 2020; Bettini, Gilmour, et al, 2020; Billingsley et al, 2020; Kaufhold et al, 2006, Mastropieri, 2001; McCarthy et al, 2016). Research also indicates that when teachers feel they have curricular resources, this may lead to (a) reduced time spent searching for and creating materials for instruction and (b) increases in teachers’ perception of well-used planning time (Bettini, Cumming, et al, 2020).…”
Section: The Importance Of Curricular Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A hearing and speech specialist has been a professional which has performed a crucial social function. The working conditions of HSSs have been examined by Billingsley et al. (2020) , who have worked to further the research agenda that have supported special educators’ work environment.…”
Section: Introductionmentioning
confidence: 99%